Approach to Loan-Words in Lithuania: A Sociolinguistic Analysis of the Attitude of Language Users - Vaicekauskienė, Loreta (Kalbotyra, 1998)
In Lithuania we have an official purist language policy, but no research has been done to find out the attitude of language users. An experiment was carried out in which 129 respondents were asked to express their opinion about loan-words in the Lithuanian language. The results of the experiment show that Lithuanians have a rather negative attitude towards borrowings. However, the attitude also depends on sex, education and age in particular: in the group of ageing people one may expect more negative feelings towards loan-words, inclination not to accept them in the public use of the language. Among the elderly population there are more people who believe that loan-words should be replaced by new Lithuanian coineers. On the other hand, the negative attitude is characteristic not only of older Lithuanians in general, but also of those with academic education, those with insufficient knowledge of English and especially of women.